PCDTBT based solar cells: one year of operation under real-world conditions - Zhang, Yiwei (Sci Rep, 2016)
We present measurements of the outdoor stability of PCDTBT:PC(71)BM based bulk heterojunction organic solar cells for over the course of a year. We find that the devices undergo a burn-in process lasting 450 hours followed by a T(S)80 lifetime of up to 6200 hours. We conclude that in the most stable devices, the observed T(S)80 lifetime is limited by thermally-induced stress between the device layers, as well as materials degradation as a result of edge-ingress of water or moisture through the encapsulation.